Early rheumatoid arthritis treated with tocilizumab, methotrexate, or their combination (U-Act-Early): a multicentre, randomised, double-blind, double-dummy, strategy trial. Issue 10042 (23rd July 2016) - Bijlsma, Johannes W J; Welsing, Paco M J; Woodworth, Thasia G; Middelink, Leonie M; Pethö-Schramm, Attila; Bernasconi, Corrado; Borm, Michelle E A; Wortel, Cornelis H; ter Borg, Evert Jan; Jahangier, Z Nazira; van der Laan, Willemijn H; Bruyn, George A W; et al.
Summary: Background: For patients with newly diagnosed rheumatoid arthritis, treatment aim is early, rapid, and sustained remission. We compared the efficacy and safety of strategies initiating the interleukin-6 receptor-blocking monoclonal antibody tocilizumab with or without methotrexate (a conventional synthetic disease-modifying antirheumatic drug [DMARD]), versus initiation of methotrexate monotherapy in line with international guidelines. Methods: We did a 2-year, multicentre, randomised, double-blind, double-dummy, strategy study at 21 rheumatology outpatient departments in the Netherlands. We included patients who had been diagnosed with rheumatoid arthritis within 1 year before inclusion, were DMARD-naive, aged 18 years or older, met current rheumatoid arthritis classification criteria, and had a disease activity score assessing 28 joints (DAS28) of at least 2·6. We randomly assigned patients (1:1:1) to start tocilizumab plus methotrexate (the tocilizumab plus methotrexate arm), or tocilizumab plus placebo-methotrexate (the tocilizumab arm), or methotrexate plus placebo-tocilizumab (the methotrexate arm). Tocilizumab was given at 8 mg/kg intravenously every 4 weeks with a maximum of 800 mg per dose. Methotrexate was started at 10 mg per week orally and increased stepwise every 4 weeks by 5 mg to a maximum of 30 mg per week, until remission or dose-limiting toxicity. We did the randomisation using an interactive web response system. Masking was achieved with placebos that were similar in appearance to the active drug; the study physicians, pharmacists, monitors, and patients remained masked during the study, and all assessments were done by masked assessors. Patients not achieving remission on their initial regimen switched from placebo to active treatments; patients in the tocilizumab plus methotrexate arm switched to standard of care therapy (typically methotrexate combined with a tumour necrosis factor inhibitor). When sustained remission was achieved, methotrexate (and placebo-methotrexate) was tapered and stopped, then tocilizumab (and placebo-tocilizumab) was also tapered and stopped. The primary endpoint was the proportion of patients achieving sustained remission (defined as DAS28 <2·6 with a swollen joint count ≤four, persisting for at least 24 weeks) on the initial regimen and during the entire study duration, compared between groups with a two-sided Cochran-Mantel-Haenszel test. Analysis was based on an intention-to-treat method. This trial was registered atClinicalTrials.gov, numberNCT01034137 . Findings: Between Jan 13, 2010, and July 30, 2012, we recruited and assigned 317 eligible patients to treatment (106 to the tocilizumab plus methotrexate arm, 103 to the tocilizumab arm, and 108 to the methotrexate arm). The study was completed by a similar proportion of patients in the three groups (range 72–78%). The most frequent reasons for dropout were adverse events or intercurrent illness: 27 (34%) of dropouts, and insufficient response: 26 (33%) of dropouts. 91 (86%) of 106 patients in the tocilizumab plus methotrexate arm achieved sustained remission on the initial regimen, compared with 86 (84%) of 103 in the tocilizumab arm, and 48 (44%) of 108 in the methotrexate arm (relative risk [RR] 2·00, 95% CI 1·59–2·51 for tocilizumab plus methotrexate vs methotrexate, and 1·86, 1·48–2·32 for tocilizumab vs methotrexate, p<0·0001 for both comparisons). For the entire study, 91 (86%) of 106 patients in the tocilizumab plus methotrexate arm, 91 (88%) of 103 in the tocilizumab arm, and 83 (77%) of 108 in the methotrexate arm achieved sustained remission (RR 1·13, 95% CI 1·00–1·29, p=0·06 for tocilizumab plus methotrexate vs methotrexate, 1·14, 1·01–1·29, p=0·0356 for tocilizumab vs methotrexate, and p=0·59 for tocilizumab plus methotrexate vs tocilizumab). Nasopharyngitis was the most common adverse event in all three treatment groups, occurring in 38 (36%) of 106 patients in the tocilizumab plus methotrexate arm, 40 (39%) of 103 in the tocilizumab arm, and 37 (34%) of 108 in the methotrexate arm. The occurrence of serious adverse events did not differ between the treatment groups (17 [16%] of 106 patients in the tocilizumab plus methotrexate arm vs 19 [18%] of 103 in the tocilizumab arm and 13 [12%] of 108 in the methotrexate arm), and no deaths occurred during the study. Interpretation: For patients with newly diagnosed rheumatoid arthritis, strategies aimed at sustained remission by immediate initiation of tocilizumab with or without methotrexate are more effective, and with a similar safety profile, compared with initiation of methotrexate in line with current standards. Funding: Roche Nederland BV.